A Novel Reduced Component High Boost Multilevel Inverter - Pratik Kar; Rachita Ruchismita Sarangi; Durgesh Prasad Bagarty; Prakash Kumar Ray; Asit Mohanty; Manzoore Elahi M. Soudagar; Yasser Fouad; Sagar Shelare (IEEE Access)
This multilevel inverter produces a multi-stepped output voltage based on series connection of power cells making the use of standard low voltage components. The proposed topology uses only one voltage source and with combination of capacitors and is able to produce maximum boost with reduced number of components and voltage stress. One module can generate 7 voltage levels by using one DC power supply and two capacitors. This paper also proposes suitable ways of extension to achieve higher voltage levels thereby making the harmonic distortion very low. The proposed topology specifically addresses a very potential problem associated with capacitor type inverter that is unsteadiness or disproportionate discharge of capacitor voltage. Another potential problem is high inrush current during charging and this is also addressed in a unique. A comprehensive comparison between the proposal and other capacitor based multilevel inverter topologies is carried out based on number of components, voltage stress, cost function and other performance parameters. The main novelty lies in the reduction in number of components, multiple extension variants basic topology, addressing capacitor voltage imbalance and high inrush current during charging. Finally, the working, efficiency and accuracy of the proposed inverter are validated by laboratory prototype models.